MOBILE MARKETING STRATEGIES AND CUSTOMER PATRONAGE OF MOBILE TELECOMMUNICATION SERVICES - Nkpurukwe, Obabuike Ikeni; Amangala, Emmanuel A.; Wali, Andy Fred (International Journal of Marketing Research Innovation, 2020)
This study empirically examines the relationship between mobile marketing strategies and customer patronage of mobile telecommunication services. The study applied a cross-sectional survey design in a structured questionnaire to collect data from 400 accessible telecom subscribers across the 4 major telecom operators which include; MTN, Glo, Aitel, and 9 Mobile. A total of 4 hypotheses were proposed and Spearman’s Rank Correlation Coefficient tool was employed with the help of SPSS version 21.0, in statistically testing them. Findings revealed a positive and significant relationship between the dimensions of mobile marketing strategies and measures of customer patronage. The study, therefore, concludes that mobile marketing is an effective tool in improving purchase intention and referral. Therefore, the research recommends that telecom operators who want to improve patronage of subscribers should adopt mobile websites and SMS marketing; as these tools have been further verified to have a huge capacity to enhance purchase intention and customer referral.